Computational fluid dynamics modeling of thermal parameters and airflows and design improvement of naturally ventilated swine facilities in tropical climates - Torres Cordero, Harold Arley (Universidade Federal de Viçosa, 2023)
Mathematical techniques, such as Computational Fluid Dynamics (CFD), are being increasingly applied as a basis for designing facilities for animal production, as well as for guidance on the respective ambience. As a result, economy and speed have been achieved in the choice and design of construction typologies, as well as improvements in decision-making related to the well-being of animals and workers throughout the production chain. However, studies on the use of CFD for modeling processes in traditional pork production in regions with tropical and subtropical climates, such as Brazil and Colombia, are still limited. The objective of this investigation was to evaluate thermal comfort and air flow in three different types of pig housing construction, typical of Colombia, naturally ventilated and with different thermal floors (cold, mild, and warm), used in the fattening phase. Then, the objective was to propose improvement of the thermal conditions in the environment of those facilities, based on the Temperature and Humidity Index (THI). The three typical facilities used were selected from a set of ten covered in a previous study. In the present study, pigs at the beginning of the fattening phase, with an average of 70 kg of body weight, were used. To validate the information related to the thermal environment, air temperature (T), relative humidity (RH) and air velocity (v) data were collected at different points, uniformly distributed inside each of the different facilities. For this, a low-cost sensor, specifically developed for the study. CFD was used to model and simulate the variation of such parameters for different typologies. After that, a comparison was made with the field data, verifying the correspondence between them, based on the Normalized Mean Squared Error (NMSE), used to validate the information obtained by the simulation. For the typologies of pig facilities with the worst average conditions (THI below 74), improvements in hygrometric and thermal conditions were proposed, via simulation of the application of a ventilation system associated with an evaporative cooling system. It was verified that, with this study, it was possible to validate the modeling conducted via CFD, observing statistically acceptable values of the modeled parameters, thermaland air flow, in comparison with those obtained in the field conditions. Alternative ventilation and evaporative cooling systems were proposed for two of the analyzed production facilities, in which it was possible to reduce more than 4.8°C in temperature and add more than 0.40 m/s in air flow, in both cases. As a result, there was a reduction in the triggering of comfort alarms in these pork production units. Keywords: simulation, mathematical techniques, rural constructions, pig Facilitying, animal ambience, ventilation.

Técnicas matemáticas, tais como a Dinâmica de Fluidos Computacional (CFD), vêm sendo cada vez mais aplicadas como base para projetos de instalações para produção animal, bem como para orientação acerca da respectiva ambiência. Com isso, tem- se atingido economia e rapidez na escolha e concepção das tipologias das construções, bem como melhorias na tomada de decisão relacionadas ao bem-estar animal e dos trabalhadores de toda a cadeia produtiva. Contudo, ainda são restritos os estudos relativos ao emprego de CFD para modelagem de processos na produção tradicional de suínos em regiões de climas tropicais e subtropicais, a exemplo do Brasil e da Colômbia. O objetivo desta investigação foi avaliar o conforto térmico e o fluxo de ar em três diferentes tipologias construtivas de alojamentos de suínos, típicas da Colômbia, naturalmente ventiladas e com distintos pisos térmicos (frio, temperado e quente), utilizadas na fase de terminação. Em seguida, objetivou-se propor melhoria das condições térmicas no ambiente daquelas instalações, com base no Índice de Temperatura e Umidade (THI). As três instalações típicas utilizadas foram selecionadas de um conjunto de dez abordadas em um estudo anterior. No presente estudo foram utilizados suínos em início da fase de engorda, com 70kg de peso corporal, em média. Para validar as informações relativas ao ambiente térmico, dados de Temperatura do ar (T), Umidade Relativa do ar (RH) e velocidade do ar (v), foram coletados em diferentes pontos, uniformemente distribuídos no interior de cada uma das diferentes instalações. Para isso, foi utilizado um sensor de baixo custo, especificamente desenvolvido para o estudo. CFD foi utilizada para modelar e simular a variação de tais parâmetros para as diferentes tipologias. Após isso, foi feita a comparação com os dados de campo, verificando-se a correspondência entre os mesmos, com base no Erro Quadrático Médio Normalizado (NMSE), utilizado para validar as informações obtidas pela simulação. Para as tipologias de instalações suinícolas com as piores condições médias (THI abaixo de 74), foram propostas melhorias das condições higrométricas e térmicas, via simulação de aplicação desistema de ventilação associado à sistema de resfriamento evaporativo. Verificou-se que, com este estudo, foi possível validar a modelagem realizada via CFD, observando-se valores dos parâmetros modelados, térmicos e de fluxo de ar, estatisticamente aceitáveis, em comparação com os obtidos nas condições de campo. Foram propostas alternativas de sistemas de ventilação e de resfriamento evaporativo para duas das instalações de produção analisadas, nas quais se conseguiu reduzir mais de 4.8°C na temperatura e acrescentar mais de 0,40m/s no fluxo de ar, em os ambos casos. Com isso, houve redução no acionamento de alarmes de conforto nessas unidades de produção de carne suína. Palavras-chave: simulação, técnicas matemáticas, construções rurais, suinocultura, ambiência animal, ventilação.
Modelagem por dinâmica computacional de fluidos de parâmetros térmicos e de fluxos de ar e melhoria projetual de instalações de suinos naturalmente ventiladas em climas tropicais
Keywords: Contruções rurais - Aquecimento e ventilação; Métodos de simulação; Modelos matemáticos; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::CONSTRUCOES RURAIS E AMBIENCIA